IMPACT OF AUDITORâS WORK EXPERIENCE, INDEPENDENCE, OBJECTIVITY, INTEGRITY, COMPETENCY AND ACCOUNTIBILITY ON AUDIT QUALITY - Ningrum, Gita Sulistya; Wedari, Linda Kusumaning (Journal Economics & Business Atmajaya Indonesia, 2017)
The objective of this research is to observe the impact of auditorâs work experience, independence, objectivity, integrity, competency and accountability on audit quality.     The population considered in this research consists of active auditors who work in public accounting offices in Indonesia. We use convenience sampling as our sampling method. The sample size in this research is 175 auditors. By using multiple linear regression, we found the R-squared value to be 0.828 or 82.8%, and it shows that work experience, independence, objectivity and accountability have significant impacts on audit quality, but the impacts of integrity and competency on audit quality are statistically insignificant.